Projected loss of brown macroalgae and seagrasses with global environmental change - Federica Manca; Lisandro Benedetti-Cecchi; Corey J. A. Bradshaw; Mar Cabeza; Camilla Gustafsson; Alf M. Norkko; Tomas V. Roslin; David N. Thomas; Lydia White; Giovanni Strona (Nature Communications, 2024)
Abstract Although many studies predict extensive future biodiversity loss and redistribution in the terrestrial realm, future changes in marine biodiversity remain relatively unexplored. In this work, we model global shifts in one of the most important marine functional groups—ecosystem-structuring macrophytes—and predict substantial end-of-century change. By modelling the future distribution of 207 brown macroalgae and seagrass species at high temporal and spatial resolution under different climate-change projections, we estimate that by 2100, local macrophyte diversity will decline by 3–4% on average, with 17 to 22% of localities losing at least 10% of their macrophyte species. The current range of macrophytes will be eroded by 5–6%, and highly suitable macrophyte habitat will be substantially reduced globally (78–96%). Global macrophyte habitat will shift among marine regions, with a high potential for expansion in polar regions.